Manufacturing method of annealed quartz glass cloth
The annealed quartz glass cloth addresses high dielectric loss and strength issues by heat-treating and etching quartz glass cloth, achieving low dielectric loss tangent and high tensile strength, suitable for 5G communication boards with reduced radiation and improved flexibility.
Patent Information
- Application Number
- JP2023103760
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-06-23
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-06-17
AI Technical Summary
Conventional glass cloths used in high-speed communications like 5G suffer from high dielectric loss tangents and insufficient tensile strength, especially when subjected to high frequencies and heat treatments, leading to increased transmission loss and reduced durability.
An annealed quartz glass cloth is produced by heat-treating quartz glass cloth at 500°C to 1500°C, followed by etching with specific solutions to remove silanol groups and strained layers, resulting in a dielectric loss tangent less than 0.0010 and tensile strength of 1.0N/25mm or more, using materials with high purity and controlled impurity levels.
The annealed quartz glass cloth achieves low dielectric loss tangent and high tensile strength, suitable for high-speed communication boards, with improved flexibility and reduced radiation, enabling stable production and application in 5G technologies.
Smart Images

Figure 0007611965000001 
Figure 0007611965000002 
Figure 0007611965000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an annealed quartz glass cloth and a method for producing the same. [Background technology]
[0002] Currently, with the advent of high-speed communications such as 5G, there is a strong demand for high-speed communication boards and antenna boards that have low transmission loss even when using high frequencies such as millimeter waves. In addition, there has been a remarkable trend toward high-density mounting and ultra-thinning of wiring boards in information terminals such as smartphones.
[0003] Currently, for high-speed communications such as 5G, laminates are widely used that are made by laminating prepregs obtained by impregnating low-dielectric glass cloth such as D glass, NE glass, and L glass with thermoplastic resins such as fluororesin and polyphenylene ether, and even thermosetting resins such as low-dielectric epoxy resin and low-dielectric maleimide resin, and then curing them under heat and pressure. It is known that the signal transmission loss is improved as the dielectric constant (ε) and dielectric tangent (tan δ) of the material are smaller, as indicated by the Edward A. Wolff equation: transmission loss ∝√ε×tan δ.
[0004] For this reason, glass cloths with improved dielectric properties, such as D glass, NE glass, and L glass, which have glass compositions different from E glass, have been proposed (Patent Documents 1 to 3). However, the dielectric tangent of each type of glass is large, at about 0.002 to 0.005 in the high frequency range of 10 G or more. When high frequencies such as millimeter waves are used for communication, the transmission loss is large and accurate information cannot be transmitted. Although Patent Document 4 refers to a low dielectric constant, it does not mention the dielectric tangent, which contributes more to transmission loss, and achieving a low dielectric tangent remains a difficult task.
[0005] In addition, in Patent Document 1, quartz glass fiber produced by the sol-gel method is heated and sintered to produce quartz glass fiber with a moisture content of 1000 ppm or less. The moisture content of the quartz glass fiber after heat treatment is described, but the amount of silanol (Si-OH) and the dielectric tangent are not mentioned. Since it is produced by the sol-gel method, the moisture and silanol groups attached to the gel are not separated.
[0006] In general, infrared spectroscopy such as diffuse reflectance IR spectroscopy uses wavelengths from 3000 to 3700 cm -1 The silanol concentration is measured by utilizing the infrared absorption of silanol groups at 3000 to 3700 cm. It is also known that the position of infrared absorption varies depending on the form of silanol groups in silica (see Patent Document 5). For this reason, for silanols present in quartz glass in various forms, it is necessary to first identify the infrared absorption spectrum to which they belong, and then quantify the amount of silanol in each form by measuring the transmittance of the corresponding peak. However, it is difficult to quantify silanols in the range of 3000 to 3700 cm. -1 When measuring the silanol group concentration using infrared absorption of silanol groups at 3660 cm, the infrared absorption in the above wave number region overlaps with the absorption by the hydroxyl groups of water, so the influence of the coexisting water is unavoidable, making it difficult to accurately measure the silanol groups present in quartz. In particular, although Patent Document 1 employs the diffuse reflectance IR method, it uses a 3660 cm infrared spectrometry without considering the influence of the coexisting water. -1 The water content is calculated using only the silanol peak, and no distinction is made between the water content and the silanol content in the silica glass (OH of silanol cannot be distinguished from OH derived from HO).
[0007] Furthermore, although Patent Document 1 shows the relationship between the moisture content and the dielectric loss tangent in the quartz glass fiber, there is no mention of the silanol content, and the dielectric loss tangent is a value measured on a printed circuit board using quartz glass fiber and PTFE, so the correlation between the silanol content and the dielectric loss tangent of the glass fiber is not made clear. Also, although it is mentioned that the yarn strength (tensile strength) drops rapidly when sintered at 1200°C or higher, there is no mention at all of the recovery of strength.
[0008] In general, the amount of hydroxyl groups (OH groups) remaining in silica glass varies depending on the manufacturing method and heat treatment, and it is known that differences in OH concentration bring about various differences in the physical properties of silica glass (Non-Patent Document 1). However, it is not known that the amount of OH can be reduced to a predetermined amount by high-temperature treatment in order to improve the dielectric tangent. In addition, when hydroxyl-containing quartz glass is heat-treated at high temperatures, the amount of distortion increases, especially on the glass surface (Non-Patent Document 2), and the strength is greatly reduced. For this reason, heat-treated quartz glass cloth (annealed quartz glass cloth) has not been put to practical use. Moreover, at present, nothing is known at all about the recovery of strength of quartz products, including quartz glass cloth, after high-temperature heat treatment. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Japanese Patent Application Publication No. 5-170483 [Patent Document 2] JP 2009-263569 A [Patent Document 3] JP 2009-019150 A [Patent Document 4] JP 2018-197411 A [Patent Document 5] Japanese Patent Application Publication No. 2-289416 [Non-patent literature]
[0010] [Non-Patent Document 1] Change in OH group concentration in silica glass due to heat treatment February 2011, Master's thesis, Graduate School of Engineering, Fukui University [Non-Patent Document 2] Structural Changes of Silica Glass Blocks by Heat Treatment, February 2005, Master's thesis, Graduate School of Engineering, Fukui University Summary of the Invention [Problem to be solved by the invention]
[0011] Conventional technology has a problem in that it is not possible to obtain low dielectric tangent glass cloth that satisfies both the dielectric properties and tensile strength required for high-speed communications such as 5G. The present invention has been made to solve the above problems, and has as its object to provide an annealed quartz glass cloth having a low dielectric tangent and excellent tensile strength, and a method for producing annealed quartz glass cloth whose strength is restored after high-temperature heat treatment. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides an annealed quartz glass cloth that has been subjected to a heat treatment, the SiO2 content being 99.5 mass% or more, the dielectric loss tangent at 10 GHz being less than 0.0010, and the tensile strength being 100% by weight of the cloth (g / m 2 ), i.e., the tensile strength is 1.0N / 25mm or more per cloth weight (g / m 2 The present invention provides an annealed quartz glass cloth having a compressive strength of 1.0 N / 25 mm or more.
[0013] Such an annealed quartz glass cloth has a low dielectric tangent and excellent tensile strength.
[0014] Here, the dielectric tangent is preferably 0.0008 or less.
[0015] In this way, the present invention makes it possible to make the dielectric tangent of the annealed quartz glass cloth less than 0.0010, approaching the level of original quartz.
[0016] The tensile strength is also determined by the cloth weight (g / m 2 ) is preferably 1.2N / 25mm or more.
[0017] Such a tensile strength provides a substrate or the like with even greater strength.
[0018] In the present invention, the silanol group (Si-OH) concentration is preferably 300 ppm or less.
[0019] Such an annealed quartz glass cloth would have a lower dielectric tangent.
[0020] It is also preferable that the total alkali metal content is 10 ppm or less, each of the B and P contents is 1 ppm or less, and each of the U and Th contents is 0.1 ppb or less.
[0021] Such a material has an extremely high purity compared to conventional quartz glass cloth and emits very little radiation such as alpha rays, making it an ideal material for preventing soft errors when used in circuit boards for servers and other devices.
[0022] Furthermore, it is preferable that when the quartz glass cloth is bent around a mandrel having a diameter of 2.5 mm or more or folded 180 degrees in accordance with JIS K 5600-5-1, general coating material test method for bending resistance, there are no breaks or bending marks.
[0023] Such a material has a low dielectric tangent, high tensile strength, and excellent flexibility, and therefore has high added value.
[0024] In addition, the present invention provides a method for producing a quartz glass cloth having a dielectric loss tangent of less than 0.0010 at 10 GHz and a tensile strength of less than 0.0010 (g / m2) of the cloth weight, by heat-treating the quartz glass cloth at a temperature of 500°C to 1500°C and then etching the surface of the heat-treated quartz glass cloth with an etching solution. 2 The present invention provides a method for producing an annealed quartz glass cloth, which is characterized by producing an annealed quartz glass cloth having a strength of 1.0 N / 25 mm or more per tensile strength.
[0025] Such a method for producing annealed quartz glass cloth allows the strength to be restored after high-temperature heat treatment, so that annealed quartz glass cloth with a low dielectric tangent and excellent tensile strength can be reliably obtained.
[0026] Here, it is preferable to use, as the etching solution, an aqueous solution selected from the group consisting of an aqueous hydrofluoric acid solution, an aqueous ammonium fluoride solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, an aqueous sodium carbonate solution, an aqueous ammonia solution, and an alkaline electrolytic water.
[0027] Such an etching solution is preferable as it removes the distorted layer of the quartz glass cloth and restores its strength.
[0028] In this case, it is preferable to use a basic aqueous solution having a pH of 11 or more as the etching solution, and it is more preferable to use alkaline electrolytic water having a pH of 12 or more.
[0029] Such an etching solution is more preferable from the viewpoints of the etching effect on quartz glass and improvement of tensile strength, and alkaline electrolyzed water with a pH of 12 or more is even more preferable from the viewpoints of the working environment and wastewater treatment.
[0030] It is also preferable that the etching treatment is carried out in a continuous process.
[0031] Such a manufacturing method can improve the productivity of annealed quartz glass cloth.
[0032] Furthermore, it is preferable to treat the surface of the etched quartz glass cloth with a coupling agent.
[0033] Coating the surface of the quartz glass cloth with a silane coupling agent in this way has the effect of increasing the slipperiness and wettability of the glass cloth and yarn, and increasing the tensile strength of the glass cloth. In addition, when manufacturing prepregs, the adhesion between the resin and the glass cloth surface can be strengthened. Effect of the Invention
[0034] As described above, the annealed quartz glass cloth of the present invention has a low dielectric tangent and high tensile strength, so that a communication board impregnated with resin can be produced as an ideal board with low transmission loss. Furthermore, the manufacturing method of the annealed quartz glass cloth of the present invention can recover strength by etching after high-temperature heat treatment, so that an annealed quartz glass cloth with a low dielectric tangent and excellent tensile strength can be reliably obtained, and productivity is also excellent. Furthermore, the annealed quartz glass cloth of the present invention is also excellent in flexibility, so that it is highly useful in fields such as high-speed communication. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] As described above, there has been a demand for the development of a low dielectric tangent glass cloth that satisfies both the dielectric properties and tensile strength required for high-speed communications.
[0036] As a result of extensive research into how to bring the dielectric tangent of quartz glass cloth closer to the inherent value of quartz, the inventors discovered that annealed quartz glass cloth with high strength and low dielectric tangent can be obtained by heating and removing the silanol groups remaining in the quartz that constitutes the quartz glass cloth at high temperatures, and then dissolving and removing the surface layer of the quartz glass filaments, etc. that constitute the cloth, thereby completing the present invention.
[0037] That is, the present invention provides an annealed quartz glass cloth obtained by subjecting a quartz glass cloth to a heat treatment, the SiO2 content being 99.5 mass% or more, the dielectric loss tangent at 10 GHz being less than 0.0010, and the tensile strength being 100% by weight of the cloth (g / m 2 ) is 1.0 N / 25 mm or more.
[0038] The present invention will be described in detail below, but the present invention is not limited thereto.
[0039] The annealed quartz glass cloth of the present invention is a quartz glass cloth that has been subjected to a heat treatment (500 to 1500°C), and has a dielectric loss tangent (10 GHz) of less than 0.0010, preferably a dielectric loss tangent of 0.0008 or less, more preferably a dielectric loss tangent of 0.0005 or less, and even more preferably a tensile strength of 0.0002 or less, and a cross weight (g / m 2 ) and preferably 1.0N / 25mm or more per cloth weight (g / m 2 ) is 1.2N / 25mm or more. Furthermore, the annealed quartz glass cloth has an SiO2 content of 99.5 mass % or more. If the SiO2 content is lower than this, a low dielectric tangent comparable to that of quartz cannot be obtained even after heat treatment. The annealed quartz glass cloth in the present invention refers to a quartz glass cloth that has been subjected to a heat treatment at 500°C to 1500°C, and as described below, is a quartz glass cloth itself that has been subjected to a heat treatment. Therefore, it is clearly different from quartz glass obtained by high-temperature treatment of fused silica or sol-gel silica, which is treated at high temperatures during the manufacturing process of the glass cloth itself. Hereinafter, annealed quartz glass cloth may be simply referred to as quartz glass cloth. As described later, the dielectric tangent can be measured using split post dielectric resonators (SPDRs) for measuring dielectric constant at a dielectric resonator frequency of 10 GHz, and the tensile strength is measured in accordance with "7.4 Tensile strength" of JIS R3420:2013 "General test methods for glass fibers."
[0040] The quartz glass material used in the manufacture of the annealed quartz glass cloth of the present invention can be primarily natural quartz with few impurities or synthetic quartz made from raw materials such as silicon tetrachloride, etc. The main component is SiO2 at 99.5 mass% or more. It is more preferable that the total concentration of impurities in the quartz glass material, such as alkali metals Na, K, Li, etc., is 10 ppm or less, B (boron) is 1 ppm or less, P (phosphorus) is 1 ppm or less, and in order to prevent malfunction due to radiation, the content of U and Th is each 0.1 ppb or less. By using such a quartz glass material, it is possible to obtain an annealed quartz glass cloth with a total alkali metal content of 10 ppm or less, a content of B and P of 1 ppm or less, and a content of U and Th of 0.1 ppb or less. The concentration of the above impurities can be measured by atomic absorption spectrometry or inductively coupled plasma (ICP) atomic emission spectrometry. For example, it can be obtained from a calibration curve prepared in advance using a sample with a known concentration using an apparatus such as ICP-AES or ICP-MS.
[0041] The annealed quartz glass cloth of the present invention can be produced by producing filaments, strands and yarns from a quartz ingot obtained by the following method, and weaving the filaments, strands and yarns.
[0042] Quartz ingots can be produced by the electric melting method or the flame melting method using naturally occurring quartz as the raw material, or by the direct synthesis method, the plasma synthesis method, the soot method, or the sol-gel method using alkyl silicate as the raw material. For example, quartz yarns with a diameter of 100 to 300 μm that can be used in the present invention can be produced by melting an ingot at 1700 to 2300°C, stretching it, and winding it up. Since quartz yarns are hard and inelastic, it is desirable to coat them with a resin to prevent them from breaking when being wound up. As the coating agent, a UV-curable resin with an acrylate functional group that has excellent curing properties is preferred. The thickness of the coating is preferably 5 μm or more. If it is 5 μm or more, the thickness is sufficient and a high reinforcing effect can be obtained.
[0043] In this specification, the thin thread-like single fiber obtained by stretching the above-mentioned quartz yarn is defined as a quartz glass filament, a bundle of quartz glass filaments is defined as a quartz glass strand, and a bundle of quartz glass filaments that are further twisted is defined as a quartz glass yarn.
[0044] In the case of quartz glass filaments, the diameter is preferably 3 μm to 20 μm, more preferably 3.5 μm to 9 μm. Methods for producing quartz glass filaments include the above-mentioned electric melting of quartz yarns and drawing with oxyhydrogen flame, but the method is not limited to these methods as long as the diameter of the quartz glass filaments is 3 μm to 20 μm.
[0045] The quartz glass strand is produced by bundling 10 to 400 of the quartz glass filaments, preferably 40 to 200 of the quartz glass filaments, together.
[0046] The annealed quartz glass cloth of the present invention can be produced by weaving the above-mentioned quartz glass yarn or strand.
[0047] In the present invention, the number of twists of the quartz glass yarn is not particularly limited, but a small number of twists makes it easier to make the cloth thinner and to reduce the air permeability in the opening process after the glass cloth is made. A large number of twists increases the yarn convergence, making it less likely to break or fluff. The quartz glass yarn is woven into a glass cloth with warp and weft weaving densities of 10 threads / 25 mm or more, preferably 30 threads / 25 mm or more, more preferably 50 threads / 25 mm or more, and 120 threads / 25 mm or less, preferably 110 threads / 25 mm or less, more preferably 100 threads / 25 mm or less.
[0048] The method for weaving the quartz glass cloth is not particularly limited, and examples thereof include a method using a rapier loom, a shuttle loom, and an air jet loom. Generally, when manufacturing cloth, in order to prevent the yarn from becoming frayed or breaking, the yarn is woven using yarn whose filament surface is coated with a sizing agent whose main component is starch as a film-forming agent. The sizing agent may contain other components other than starch, such as a cationic vinyl acetate copolymer emulsion. Examples of other components include lubricants, emulsifiers, cationic softeners, antistatic agents, silane coupling agents, preservatives, etc. A small amount of alcohol, such as methanol, ethanol, isopropanol, or other organic solvents may be added to the sizing agent for quartz glass fibers of the present invention.
[0049] As a method for removing the sizing agent after weaving, there are general methods such as dissolving in a solution or burning off by heating, but a method using a sizing agent made of water-soluble fibers and dissolving and removing it with hot water is particularly preferable. This method not only removes the sizing agent, but also causes the filaments of the strands that make up the glass cloth to be in a spread-out state, i.e., a fiber-opening process, and furthermore, due to the unexpected presence of small gaps caused by the removal of the sizing agent, the spread-out filaments become wavy. As a result, it is possible to obtain a smooth cloth with a relatively uniform density and small surface irregularities, despite a small basis weight and number of filaments.
[0050] If heat cleaning such as heat treatment is performed after weaving, the stains can be removed by storing the fabric at a temperature of 200°C or higher and lower than 500°C for 24 to 100 hours. The tensile strength of the quartz glass cloth in this state is the cloth weight (g / m 2 ) is 1.0N / 25mm or more, which is not at a level that would cause problems when handling in the next process.
[0051] Currently available quartz glass cloth obtained by this type of manufacturing method has better dielectric properties than LE glass, known as low dielectric glass, but its dielectric dissipation factor is 0.0010 or more, which is larger than the dielectric dissipation factor of 0.0001 inherent to quartz.
[0052] The inventors have succeeded in increasing the tensile strength of the quartz glass cloth by increasing the dielectric tangent in the high frequency range to the original level of quartz through high-temperature heat treatment, while increasing the tensile strength of the quartz glass cloth by increasing the cloth weight (g / m 2As a result of extensive research into obtaining a quartz glass cloth with a strength of 1.0 N / 25 mm or more per unit area, it was discovered that the strength could be significantly improved by removing the distorted layer on the surface of the fibers that make up the quartz glass cloth after high-temperature treatment. The method for producing the annealed quartz glass cloth, including the removal of the strained layer, will now be described in detail.
[0053] The method for producing annealed quartz glass cloth of the present invention comprises heat-treating a quartz glass cloth at a temperature of 500°C to 1500°C, and then etching the surface of the heat-treated quartz glass cloth with an etching solution to obtain a quartz glass cloth having a dielectric loss tangent of less than 0.0010 at 10 GHz and a tensile strength of less than 0.0010 (g / m 2 The method is characterized in that the annealed quartz glass cloth has a dielectric strength of 1.0 N / 25 mm or more per unit area. This manufacturing method includes, for example, a step (heat treatment step) of subjecting the quartz glass cloth manufactured by the above-mentioned method to heat treatment at high temperature (500 to 1500°C) to remove silanol groups (Si-OH) present in the quartz and reduce the dielectric constant, (2) a step (strength recovery step) of improving the tensile strength of the quartz glass by dissolving and removing the strained layer generated on the quartz glass surface during the high-temperature treatment by etching, and, if necessary, (3) a step (coupling agent treatment step) of treating the quartz glass cloth surface with a coupling agent or the like. In addition, other steps such as washing and drying may be included in any order as necessary.
[0054] [(1) Heat treatment process] The heat treatment step is a step in which the quartz glass cloth is heated at a high temperature to remove silanol groups present in the quartz, thereby reducing the dielectric constant. The heating temperature for removing silanol groups in quartz is 500° C. to 1500° C., preferably 500° C. to 1300° C., and more preferably 700° C. to 1000° C. As a heating method, the woven quartz glass cloth wrapped around a quartz tube or metal tube is placed in an electric heating furnace, muffle furnace, or the like, and heat-treated at 500° C. to 1500° C., but the heating method and the shape of the quartz glass cloth to be treated are not limited to these.
[0055] The heat treatment time for the quartz glass cloth varies depending on the heating temperature, but in practice, 1 minute to 72 hours is preferable, 10 minutes to 24 hours is more preferable, and 1 hour to 12 hours is even more preferable. After heating, cooling to room temperature can be done either slowly or rapidly, but since the molten quartz glass may partially crystallize depending on the conditions, it is advisable to optimize the heating temperature and cooling conditions.
[0056] The heating atmosphere is not particularly limited and may be air, an inert gas such as nitrogen, normal pressure, vacuum or reduced pressure, but is usually carried out in air at normal pressure, taking into account costs and the like.
[0057] The analytical methods for silanol groups include the Grignard reagent method and solid 29 Various analytical methods, such as Si NMR and infrared spectroscopy, have been investigated, but each has its advantages and disadvantages, so they are used appropriately. The Grignard method can quantify the amount of silanol groups, and has excellent reproducibility because it reacts efficiently with the silanol groups present on the surface of the quartz glass cloth, but it has the disadvantage of not reacting with the silanol groups present inside the quartz glass cloth. The infrared spectroscopy method can quantify the total amount of silanol groups on the surface and inside of the quartz glass cloth, but it is difficult to distinguish between surface and internal silanol groups. However, since it is easy to confirm the reduction in silanol groups, it can be confirmed whether the desired dielectric properties have been achieved. solid 29 Although Si NMR is somewhat inefficient and the analytical procedures are complicated, it is a preferred analytical method because it allows the silanol groups on the surface and inside of the quartz glass cloth to be quantified.
[0058] It is known that in the GHz range, dipoles due to polarization respond to electric fields and cause dielectric properties. Therefore, the key to achieving low dielectric properties in the GHz range is to reduce polarization from within the structure. The dielectric constant is expressed by the Clausius-Mossotti formula below, and is determined by the molar polarizability and molar volume. Therefore, the key to lowering the dielectric constant is to reduce the polarization and increase the molar volume. Dielectric constant = [1 + 2 (ΣPm / ΣVm)] / [1 - (ΣPm / ΣVm)] (Pm: molar polarizability of an atomic group, Vm: molar volume of an atomic group)
[0059] In addition, the dielectric loss tangent (tan δ) is the delay in the dielectric response to an AC electric field, and in the GHz range, the main factor is the relaxation of the dipole orientation. Therefore, in order to reduce the dielectric loss tangent, it is possible to consider a method of eliminating the dipole (making the structure close to non-polar). For these reasons, in the present invention, as an approach to lowering the dielectric properties of silica glass in the GHz range, the concentration of silanol groups, which are polar groups, is kept low.
[0060] From the above viewpoints, in the present invention, the silanol group (Si-OH) concentration in the quartz glass cloth after heat treatment is preferably 300 ppm or less, more preferably 250 ppm or less, and more preferably 100 ppm or less. In the strength recovery step described below, the strained layer on the quartz glass surface is dissolved and removed, so the silanol group concentration in the quartz glass cloth after heat treatment is preferably low. By doing so, it is possible to obtain an annealed quartz glass cloth having a lower dielectric tangent. The silanol group (Si-OH) concentration in the finally obtained annealed quartz glass cloth is preferably 300 ppm or less, more preferably 250 ppm or less, and even more preferably 100 ppm or less, as described above.
[0061] In the present invention, the silanol concentration in the quartz glass cloth after heat treatment and the annealed quartz glass cloth is measured using a solid ion exchanger capable of quantitatively measuring the silanol groups on the surface and inside of the quartz glass cloth. 29 The silanol concentration in the quartz glass is measured by Si NMR. This allows accurate understanding of the silanol concentration that affects the dielectric tangent. The measurement of the silanol concentration in the quartz glass by solid-state 29Si NMR can be performed by a known method such as the DD (Dipolar Decoupling) / MAS (Magic Angle Spinning) method (see, for example, JP 2013-231694 A and JP 2017-3429 A).
[0062] On the other hand, as described above, while infrared spectroscopic analysis such as diffuse reflectance IR spectroscopy is sufficient to detect silanol groups in a sample, it is difficult to distinguish between surface and internal silanol groups. In addition, while infrared spectroscopy is easy to use for measuring liquids and powders, solid materials such as glass cloth are easily affected by variations in the results because they must be crushed and powdered before measurement. This method is suitable for process control because it can easily confirm whether the silanol groups have been reduced and whether the desired dielectric properties have been achieved.
[0063] This heat treatment step makes it possible to reduce the dielectric tangent (10 GHz) of the quartz glass cloth to less than 0.0010, preferably 0.0008 or less, more preferably 0.0005 or less, and even more preferably 0.0002 or less.
[0064] However, the strength of the quartz glass cloth that has been made low dielectric by heat treatment at high temperatures is 2 ), the strength drops significantly to 0.5 N / 25 mm or less. As a result, it is not possible to carry out subsequent processes, such as coupling agent treatment or resin impregnation for prepreg production, and the quartz glass cloth in this state cannot be put to practical use. Therefore, in the present invention, the following strength recovery process is subsequently carried out.
[0065] [(2) Strength recovery process] Next, the process for restoring the strength of the quartz glass cloth, which is the basis of the present invention, will be described in detail. The strength recovery process is a process for improving the tensile strength of the quartz glass by dissolving and removing the strained layer that occurs on the surface of the quartz glass during high-temperature treatment. As a result of investigating the decrease in strength after heat treatment, the inventors have found that slight distortion remains in the surface layer of the quartz glass cloth after heat treatment at high temperatures, and that this distortion layer serves as the starting point for easy breakage. They have also found that in order to further restore strength, the strength can be restored by removing this distortion layer.
[0066] The strained layer of the quartz glass cloth can be easily removed by immersing it in an etching solution. The etching solution is not particularly limited as long as it can remove the strained layer, but examples of the etching solution that can be used include acidic aqueous solutions such as hydrofluoric acid, acidic ammonium fluoride (NH4F HF) and acidic potassium fluoride (KHF2) solutions, and basic aqueous solutions selected from ammonium fluoride, sodium hydroxide, potassium hydroxide, sodium carbonate, ammonia water, and alkaline electrolytic water. From the viewpoints of the working environment and wastewater treatment, alkaline electrolytic water is more preferable.
[0067] The etching conditions of the quartz glass cloth after the heat treatment are not particularly limited as long as the strained layer can be removed, but the temperature is preferably room temperature (23°C) to 100°C, more preferably 40°C to 80°C. The treatment time is not particularly limited because it depends on the etching rate of the quartz surface at the treatment temperature, but the treatment temperature is room temperature to 90°C, preferably 40°C to 80°C. The lower the temperature of the etching solution, the less etching progresses, and the higher the temperature, the faster the etching rate, but a temperature at which the treatment is completed in 10 minutes to 168 hours is desirable for practical purposes. The treatment time is preferably 1 hour to 72 hours, more preferably 10 hours to 24 hours. In addition, the treatment can be performed at the above temperature and time range even in atmospheric pressure or a pressurized atmosphere. The pH of the etching solution is not particularly limited as long as the strained layer can be removed, and may be adjusted by adding an acid or a base as necessary.
[0068] Specifically, if the basic solution has a pH of 8.0 or higher, the etching effect on the quartz glass is sufficient and an improvement in tensile strength is observed, but the pH is preferably 10.0 to 13.5, and more preferably 11.0 to 13.0. As the basic etching solution, it is preferable to use a basic aqueous solution having a pH of 11 or more, and it is more preferable to use alkaline electrolytic water having a pH of 12 or more.
[0069] The etching process is not particularly limited as long as it can remove the strained layer, but from the viewpoint of improving the productivity of the annealed quartz glass cloth, it is preferable to carry out the etching treatment in a continuous process. This can be done as follows.
[0070] The treatment method is to remove the strained layer by directly immersing a roll of quartz glass cloth wound around a metal tube or quartz tube in an etching tank filled with an etching solution, or by continuously immersing the roll in multiple etching tanks filled with different etching solutions. The treatment method is not limited as long as the specified temperature and time are satisfied. Metal tubes and quartz tubes with holes in them may be used to facilitate the penetration of the etching solution into the wound quartz glass cloth.
[0071] Alternatively, the etching process can be carried out by continuously unwinding the quartz glass cloth wound around a metal or quartz tube and passing it through the above-mentioned etching tank for a predetermined period of time. This method is preferable for uniform etching.
[0072] In order to carry out the etching smoothly, an ultrasonic generator may be installed in the etching tank and ultrasonic waves may be emitted to apply vibrations while etching. Applying ultrasonic waves is a preferred method because etching is carried out more uniformly.
[0073] After the etching treatment, in order to remove impurities such as alkali metals, the quartz glass cloth is washed in a washing tank containing pure water or ion-exchanged water at room temperature to 100° C. while in the rolled state or while being continuously unraveled and pulled out from the roll. If alkaline electrolytic water is used as the etching solution, the washing step may be omitted.
[0074] After cleaning, it is desirable to heat and dry the quartz glass cloth to remove any moisture, so that it can be sent to the next process, such as coupling agent treatment. By carrying out the etching process, the fiber opening process can be carried out at the same time.
[0075] [(3) Coupling agent treatment process] The coupling agent treatment step is a step that is carried out as necessary, and is a step of treating the surface of the quartz glass cloth with a coupling agent, etc. The coupling agent is not particularly limited, but a silane coupling agent is preferred.
[0076] Surface treatment with a silane coupling agent is effective in increasing the slipperiness and wettability of the glass cloth and yarn, and increasing the tensile strength of the glass cloth by about 1.5 to 2.5 times by coating the surface of the glass cloth with a silane coupling agent after washing and drying the quartz glass cloth that has been subjected to high-temperature treatment and etching. It is also effective in strengthening the adhesion between the resin and the glass cloth surface when manufacturing prepregs, etc.
[0077] As the silane coupling agent, a known silane coupling agent can be used, but alkoxysilane is preferred, and one or more selected from the group consisting of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, p-styryltrimethoxysilane, and trifluoropropyltrimethoxysilane are more preferred.Furthermore, amino-based alkoxysilane is more preferred.
[0078] The silane coupling agent is usually used in a dilute aqueous solution with a concentration of 0.1% to 5% by mass, but it is particularly effective to use it in a concentration of 0.1% to 1% by mass. By using the cloth according to the present invention, the silane coupling agent adheres uniformly to the glass cloth surface, providing a more uniform protective effect and improving the tensile strength, making it easier to handle, and also enabling a uniform and even application to the resin used in producing prepregs, etc.
[0079] As described above, the sintered material has a low dielectric tangent (less than 0.0010 at 10 GHz) and high tensile strength (cloth weight (g / m 2 The annealed quartz glass cloth of the present invention has a compressive strength of 1.0 N / 25 mm or more per unit area. Furthermore, since the annealed quartz glass cloth of the present invention has been subjected to the above-mentioned strength recovery process, it is excellent not only in tensile strength but also in flexibility (suppleness). The annealed quartz glass cloth of the present invention preferably shows no breaks or folding marks when the quartz glass cloth is folded around a mandrel having a diameter of 2.5 mm or more or folded 180 degrees in accordance with the bending resistance of the general coating material test method of JIS K 5600-5-1. Such a quartz glass cloth has a low dielectric tangent, high tensile strength, and excellent flexibility, thereby increasing its added value. The flexibility (suppleness) can be measured in accordance with the above standard by preparing cylinders of an appropriate diameter and bending the quartz glass cloth along each cylinder, or by bending the quartz glass cloth 180° without using cylinders.
[0080] According to the present invention, annealed quartz glass cloth with significantly improved dielectric tangent and tensile strength properties can be obtained by subjecting a quartz glass cloth to high-temperature heat treatment and then dissolving the strained layer present on the surface of the quartz glass cloth with an etching solution.
[0081] The annealed quartz glass cloth of the present invention can be used in millimeter wave antennas and high-speed communication substrates, and is expected to find application in a wide range of applications, including 5G, autonomous driving, and remote medical care, which are expected to see growth in the future.
[0082] In addition, annealed quartz glass cloth has a much higher purity than conventional glass cloth, and generates very little radiation such as alpha rays, making it an ideal material for preventing soft errors when used for quartz substrates for servers, etc. Moreover, mass production is possible, allowing for a stable supply at low cost. EXAMPLES
[0083] The present invention will be described in more detail below with reference to examples. However, it goes without saying that these examples are given for illustrative purposes and should not be construed as limiting.
[0084] In the following examples and comparative examples, the tensile strength (tensile strength), dielectric tangent (tan δ), silanol group content, and flexibility (suppleness) were measured by the following methods.
[0085] 1. Measurement of tensile strength Measurements were taken in accordance with "7.4 Tensile strength" of JIS R3420:2013 "General test methods for glass fibers."
[0086] 2. Measurement of dielectric tangent The dielectric constant was measured using split post dielectric resonators (SPDR) with a dielectric resonator frequency of 10 GHz (manufactured by Keysight Technologies, Inc.). The dielectric loss tangent in the examples and comparative examples indicates the dielectric loss tangent of the quartz glass cloth.
[0087] 3. Measurement of silanol group content solid 29 Measured by Si NMR (DD / MAS method).
[0088] 4. Measurement of flexibility (suppleness) In accordance with the bending resistance (cylindrical mandrel method) of JIS K 5600-5-1 "General test methods for paints," cylinders of Φ2.5 mm, Φ10 mm, and Φ23 mm were prepared, and the quartz glass cloth was bent along each cylinder, or the quartz glass cloth was bent 180° without using a cylinder. Thereafter, when each quartz glass cloth was returned to its flat state, its flexibility was judged based on whether it broke, had creases, or remained unchanged under each bending condition.
[0089] (Preparation Example 1: Manufacturing Example of Quartz Glass Cloth (SQ1)) The quartz glass yarn was put into a burner flame, and while being stretched, a sizing agent for quartz glass fibers was applied to produce a quartz glass strand consisting of 200 quartz glass filaments with a diameter of 7.0 μm. The obtained quartz glass strand was then twisted 0.2 times per 25 mm to produce a quartz glass yarn. The obtained quartz glass yarn was set in an air jet loom to weave a plain weave quartz glass cloth with a warp density of 60 threads / 25 mm and a weft density of 58 threads / 25 mm. The quartz glass cloth had a thickness of 0.086 mm and a cloth weight of 85.5 g / m. 2 It was. The quartz glass cloth was heat treated at 400°C for 10 hours to remove the fiber sizing agent. The dielectric tangent (10 GHz) of the quartz glass cloth after removal was 0.0011 and the tensile strength was 80 N / 25 mm. Table 1 shows the basic physical properties of the quartz glass cloth described in the preparation example. The total amount of alkali metals in the quartz glass cloth was 0.5 ppm, the amount of P (phosphorus) was 0.1 ppm, and the amount of U and Th was each 0.1 ppb. The amount of each element was measured by atomic absorption spectrometry (mass conversion).
[0090] (Preparation Example 2: Manufacturing Example of Quartz Glass Cloth (SQ2)) A quartz glass strand consisting of 200 quartz glass filaments having a diameter of 5.0 μm was prepared in the same manner as in Preparation Example 1. Next, the obtained quartz glass strand was twisted 0.4 times per 25 mm to prepare a quartz glass yarn. The obtained quartz glass yarn was set in an air jet loom to weave a plain weave quartz glass cloth with a warp density of 54 threads / 25 mm and a weft density of 54 threads / 25 mm. The quartz glass cloth had a thickness of 0.045 mm and a cloth weight of 42.5 g / m. 2 It was. The quartz glass cloth was heat-treated at 400°C for 10 hours to remove the fiber sizing agent. The dielectric tangent (10 GHz) of the quartz glass cloth after removal was 0.0011 and the tensile strength was 35 N / 25 mm. As with Preparation Example 1, the basic physical properties are shown in Table 1.
[0091] (Preparation Example 3: Manufacturing Example of Quartz Glass Cloth (SQ3)) A quartz glass strand consisting of 100 quartz glass filaments having a diameter of 5.0 μm was prepared in the same manner as in Preparation Example 1. Next, the obtained quartz glass strand was twisted 0.8 times per 25 mm to prepare a quartz glass yarn. The obtained quartz glass yarn was set in an air jet loom to weave a plain weave quartz glass cloth with a warp density of 66 threads / 25 mm and a weft density of 68 threads / 25 mm. The quartz glass cloth had a thickness of 0.030 mm and a cloth weight of 26.5 g / m. 2 It was. The quartz glass cloth was heat-treated at 400°C for 10 hours to remove the fiber sizing agent. The dielectric tangent (10 GHz) of the quartz glass cloth after removal was 0.0011 and the tensile strength was 22 N / 25 mm. As with Preparation Example 1, the basic physical properties are shown in Table 1.
[0092] Example 1 The quartz glass cloth (SQ1) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 1 was wound in a roll around a quartz tube with holes in the tube wall and placed in an electric furnace set at 700°C and heated for 5 hours. After heating, it was cooled to room temperature over 8 hours. At this point, the dielectric tangent and tensile strength of the quartz glass cloth were measured. The above-mentioned quartz glass cloth roll was then immersed for 48 hours in an etching tank filled with alkaline electrolytic water of pH 13 and heated to 40° C. to carry out an etching process. An ultrasonic oscillator was installed in the etching tank, and ultrasonic waves were applied to the etching. After etching, the cloth was washed with ion-exchanged water and dried to produce an annealed quartz glass cloth with low dielectric constant and high strength. The dielectric loss tangent (10 GHz) of the annealed quartz glass cloth was 0.0003, and the tensile strength was 118 N / 25 mm. In addition, the annealed quartz glass cloth did not crease or break even when bent 180 degrees. The measured physical properties (dielectric loss tangent, tensile strength, flexibility) are shown in Table 2.
[0093] Example 2 The quartz glass cloth (SQ1) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 1 was wound in a roll around a quartz tube with holes in the tube wall, placed in an electric furnace set at 500°C and heated for 24 hours. After heating, it was cooled to room temperature over 8 hours. Thereafter, etching and cleaning were performed in the same manner as in Example 1 under conditions in which the etching solution and the like shown in Table 2 were changed, and evaluation was performed (Examples 2-1 to 2-7).
[0094] Example 3 The quartz glass cloth (SQ1) having a width of 1.3 m and a length of 2000 m produced in Preparation Example 1 was etched and cleaned under the conditions shown in Table 3 in the same manner as in Example 1, and was evaluated (Examples 3-1 to 3-6).
[0095] Example 4 The quartz glass cloth (SQ1) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 1 was wound in a roll around a quartz tube with holes in the tube wall, and placed in an electric furnace set at 700°C and heated for 5 hours. After heating, it was cooled to room temperature over 8 hours. After that, the quartz glass cloth was etched by immersing it in alkaline electrolyzed water of pH 13 for 24 hours while unraveling it from the roll and passing it through an etching tank heated to 70° C. An ultrasonic oscillator was installed in the etching tank to apply ultrasonic waves. After etching, the cloth was passed through a cleaning tank filled with ion-exchanged water, dried, and rewound on a quartz tube to produce an annealed quartz glass cloth with low dielectric constant and high strength. The annealed quartz glass cloth had a dielectric loss tangent (10 GHz) of 0.0001 and a tensile strength of 105 N / 25 mm. In addition, when the annealed quartz glass cloth was bent 180°, it did not crease or break. The annealed quartz glass cloth was surface-treated by immersing it in a 0.5% by mass aqueous solution of KBM-903 (product name: Shin-Etsu Chemical Co., Ltd., 3-aminopropyltrimethoxysilane) for 10 minutes, and then drying it by heating at 110°C for 20 minutes. The physical properties (dielectric tangent, tensile strength, flexibility) measured, including the tensile strength, of the surface-treated annealed quartz glass cloth are shown in Table 4.
[0096] Example 5 The quartz glass cloth (SQ2) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 2 was wound in a roll around a quartz tube with holes in the tube wall, and placed in an electric furnace set at 700°C and heated for 5 hours. After heating, it was cooled to room temperature over 8 hours. Thereafter, etching was performed under the same conditions as in Example 4, and the various physical properties (dielectric tangent, tensile strength, flexibility) were measured and are shown in Table 4. The tensile strength of the annealed quartz glass cloth that was surface-treated in the same manner is also shown in Table 4.
[0097] Example 6 The quartz glass cloth (SQ3) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 3 was wound in a roll around a quartz tube with holes in the tube wall, and placed in an electric furnace set at 700°C and heated for 5 hours. After heating, it was cooled to room temperature over 8 hours. Thereafter, etching was performed under the same conditions as in Example 4, and the various physical properties (dielectric tangent, tensile strength, flexibility) were measured and are shown in Table 4. The tensile strength of the annealed quartz glass cloth that was surface-treated in the same manner is also shown in Table 4.
[0098] Comparative Example 1 The quartz glass cloth (SQ1) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 1 was wound in a roll around a quartz tube with holes in the tube wall, and placed in an electric furnace set at 700°C and heated for 5 hours. After heating, it was cooled to room temperature over 8 hours. The dielectric tangent (10 GHz) of this quartz glass cloth was reduced to 0.0002, but the tensile strength was 39 N / 25 mm. Regarding flexibility, the quartz glass cloth broke when bent 180 degrees. Furthermore, when wrapped around a cylinder with a diameter of 2.5 mm, part of the cloth cracked.
[0099] Comparative Example 2 The quartz glass cloth (SQ1) with a width of 1.3 m and a length of 2000 m produced in Preparation Example 1 was wound in a roll around a quartz tube with holes in the tube wall, and placed in an electric furnace set at 1600°C and heated for 1 hour. After heating, it was cooled to room temperature over 8 hours. After the heat treatment, the quartz glass cloth was partially fused and could not be taken out as a cloth.
[0100] The basic physical properties of the produced quartz glass cloths (SQ1-3) are shown in Table 1, Examples 1-2 in Table 2, Example 3 in Table 3, and the results of Examples 4-6 and Comparative Examples 1 and 2 in Table 4. In the table below, flexibility is represented by "O" if there is no break or bending marks, "△" if there is bending marks or partial break, and "X" if there is break.
[0101] [Table 1]
[0102] [Table 2]
[0103] [Table 3]
[0104] [Table 4]
[0105] As is clear from the results in Tables 1 to 4, the annealed quartz glass cloth of the present invention has a low dielectric tangent and excellent tensile strength. The annealed quartz glass cloth of Examples 1 to 6 showed no breakage or bending marks in the 180° bending test, and have excellent flexibility. By carrying out an etching treatment that restores strength after high-temperature heat treatment as in the present invention, a quartz glass cloth that combines excellent tensile strength and flexibility while maintaining a low dielectric tangent can be obtained. In particular, when the surface of the etched quartz glass cloth is further treated with a coupling agent, the slipperiness and wettability of the glass cloth and yarn are improved, and the tensile strength of the glass cloth increases by about 2 to 2.5 times (cloth weight (g / m)) compared to before the coupling agent treatment. 2 ) to 2.5N / 25mm or more. On the other hand, in Comparative Example 1, which was only subjected to high-temperature heat treatment and not etching treatment, the dielectric tangent was low, but the tensile strength was low and the flexibility was poor, making it unsuitable for practical use. In Comparative Example 2, the heat treatment temperature was too high, so it was not possible to take out the cloth in the first place.
[0106] In this way, the annealed quartz glass cloth of the present invention has a low dielectric tangent, excellent tensile strength, and flexibility by performing an etching treatment that restores the strength after high-temperature heating. Furthermore, by further treating with a coupling agent, when manufacturing prepregs, etc., it is possible to obtain a substrate with excellent properties due to the combined effect of strengthening the adhesion between the resin and the glass cloth surface and the effect of increasing the tensile strength of the glass cloth. This quartz glass cloth satisfies both the dielectric properties and tensile strength required for high-speed communication such as 5G, and is highly useful in fields such as high-speed communication where the above requirements are met.
[0107] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. The quartz glass cloth is heat-treated at a temperature of 500° C. to 1500° C., and the surface of the heat-treated quartz glass cloth is etched with an etching solution to obtain a dielectric loss tangent of less than 0.0010 at 10 GHz measured using an SPDR dielectric resonator for dielectric constant measurement, and a tensile strength of less than 0.0010 (g / m 2 annealed quartz glass cloth having a strength of 1.0 N / 25 mm or more per tensile strength of 1.0 N / 25 mm.
2. 2. The method for producing annealed quartz glass cloth according to claim 1, characterized in that the etching solution is an aqueous solution selected from the group consisting of hydrofluoric acid aqueous solution, ammonium fluoride aqueous solution, sodium hydroxide aqueous solution, potassium hydroxide aqueous solution, sodium carbonate aqueous solution, ammonia water, and alkaline electrolytic water.
3. 3. The method for producing an annealed quartz glass cloth according to claim 1, wherein a basic aqueous solution having a pH of 11 or more is used as the etching solution.
4. 4. The method for producing annealed quartz glass cloth according to claim 3, wherein the basic aqueous solution is alkaline electrolytic water having a pH of 12 or more.
5. The method for producing an annealed quartz glass cloth according to any one of claims 1 to 4, characterized in that the etching treatment is carried out in a continuous process.
6. 6. The method for producing an annealed quartz glass cloth according to claim 1, further comprising treating the surface of the etched quartz glass cloth with a coupling agent.
Citation Information
Patent Citations
Composite linen fiber filtering material
CN106139742A
Production of low silanol silica
JP1990289416A
Glass fiber for fiber reinforced plastics and fiber reinforced plastic product
JP1993170483A
Aqueous solution of glass treating agent
JP2005273080A
Heat transfer prepreg and method for producing the same and heat transfer printed circuit board using the same
JP2009019150A